Magnitude and determinant of healthcare-seeking behavior for childhood acute respiratory tract infections in Ethiopia: a cross-sectional study - Fantu Mamo Aragaw; Rediet Eristu Teklu; Meron Asmamaw Alemayehu; Nebiyu Mekonnen Derseh; Muluken Chanie Agimas; Daniel Alayu Shewaye; Atalay Liknaw Birhanie; Sintayehu Simie Tsega; Girum Shibeshi Argaw; Amensisa Hailu Tesfaye (BMC, 2024)
Abstract Background Acute respiratory infections (ARIs) remain a major public health concern which become the leading cause of mortality and morbidity in children under the age of five. A large percentage of childhood deaths and complications can be avoided by seeking proper medical care. Therefore, this study aimed to assess the magnitude, and individual and community-level determinants of mothers' healthcare-seeking behavior for their children under the age of five who had ARI symptoms in Ethiopia. Method A secondary data analysis was conducted using the 2016 Ethiopian Demographic and Health Surveys(EDHS) with a total weighted sample of 643 under-five children who had ARI symptoms within two weeks of the survey. Due to the hierarchical nature of the EDHS data, a multi-level logistic regression model was used to identify the individual and community-level factors influencing mothers' health care-seeking behavior for their children with ARI symptoms. In the multivariable multilevel analysis, those variables with a p-value < 0.05 were considered to be significant predictors of the outcome variable. Results Healthcare-seeking behavior among mothers or caregivers for children with symptoms of ARIs was 32.61% (95% CI: 29.08-36.33%) in Ethiopia. The ICC in the null model indicated that about 55% of the total variability of treatment-seeking behavior was due to differences between clusters. Child aged > 24 months [AOR = 0.35; 0.19-0.63], having primary education [AOR = 3.25; 1.27-8.32], being media exposed [AOR = 2.49; 1.15, 5.38], female household head[AOR = 3.90; 1.35, 11.24], and delivery at health institution[AOR = 2.24; 1.00, 5.01] were significant predictors of health care seeking behavior of mother for their children with ARI symptoms. Conclusion There is poor treatment-seeking behavior for children with symptoms of ARI in Ethiopia with significant community level variations. The multilevel logistic regression analysis showed that improving mothers' education, women's empowerment, facilitating institutional delivery and media accessibility are critical to promoting health-seeking behaviors among mothers or caregivers of under-five children with ARI symptoms. Hence, concerned bodies should design targeted interventions that increase mothers' or caregivers' treatment-seeking behavior for childhood ARI to reduce child morbidity and mortality.